Immune System Alterations and Postpartum Mental Illness: Evidence From Basic and Clinical Research - Dye, Courtney; Lenz, Kathryn M.; Leuner, Benedetta (Frontiers in Global Women's Health, 2022)
The postpartum period is a time associated with high rates of depression and anxiety as well as greater risk for psychosis in some women. A growing number of studies point to aberrations in immune system function as contributing to postpartum mental illness. Here we review evidence from both clinical and animal models suggesting an immune component to postpartum depression, postpartum anxiety, and postpartum psychosis. Thus far, clinical data primarily highlights changes in peripheral cytokine signaling in disease etiology, while animal models have begun to provide insight into the immune environment of the maternal brain and how central inflammation may also be contributing to postpartum mental illnesses. Further research investigating peripheral and central immune function, along with neural and endocrine interactions, will be important in successfully developing novel prevention and treatment strategies for these serious disorders that impact a large portion of new mothers.